Analisa Kapasitas Penampang Sungai Kali Gunting Di Kabupaten Jombang - Saiful Arfaah; Iswinarti (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2018)
The cause of flooding in the watershed area, one of which is caused by the inability of the river profile to accommodate the existing discharge (overflow). This research is intended to examine flood discharge and flood water level profile of Kali Gunting as a first step to determine flood mitigation solutions. Analysis of flood water level profiles using the Hec-Race 4.0 modeling program. With the help of this program, it is expected to be able to accommodate the flow parameters that are so complex. After modeling and knowing the capabilities of each part (cross section), this result will be a technical reference in determining flood mitigation measures. From the results of the study, the analysis of the potential for flooding in the scissor area was obtained as a result of the flood discharge capacity at scissors times = 301.00m3 / dt, and the emission times = 136.66m3 / dt for the 50th return period. The results of the Q50th calculation show that the condition of K. Scissors P0-P36 river water overflows / floods because the flood water level is above the eksesting embankment, while P36-P46 does not overflow / does not flood because the flood water level is below the eksesting dike. K. Panir condition P0-P48 river water overflows / floods because the flood water level is above the eksesting embankment, while P48-P60 does not overflow / does not flood because the flood water level is below the eksesting embankment